Hubungan Tingkat Pengetahuan Kesehatan terhadap Peningkatan Perilaku Hidup Bersih dan Sehat (PHBS) pada Mahasiswa - Elvira Riska Hanifah; Syva Avrillia Putri; Geulis Uthlubil Irma R; Niken Nur Indahsari; Muhamad Fadli Muzaki; Muhammad Naufal Dzaki; Muhammad Farhan Matalino; Jihan Dwi Pamungkas; Muhammad Ardabili Bai Dowi; Aditya Wahyu Prasetya; Satriya Pranata; Sarinti Sarinti (Inovasi Kesehatan Global, 2026)
Introduction: Clean and Healthy Living Behavior (PHBS) is an important indicator in improving health status, particularly among university students as a productive age group. Health knowledge plays a role as a predisposing factor in the formation of healthy behavior. Individuals with a good level of health knowledge tend to have higher awareness and motivation to implement PHBS. Conversely, a lack of knowledge may lead to behaviors that pose health risks. Objective: This study aimed to determine the relationship between the level of health knowledge and clean and healthy living behavior (PHBS) among students at Universitas Muhammadiyah Semarang. Methods: This study employed a quantitative design with a cross-sectional approach. The sample consisted of 55 students, including students from health-related and non-health-related faculties. Samples were selected using an accidental sampling technique, namely respondents who were encountered and willing to complete the questionnaire at the time of data collection. The research instruments were a health knowledge questionnaire and a PHBS questionnaire. Data analysis was conducted using univariate and bivariate analysis with the Spearman test. Results: The results showed that the majority of respondents had good health knowledge (89.1%) and good PHBS (90.9%). The Spearman test results showed a p-value of 0.001 (p < 0.05), indicating a significant relationship between the level of health knowledge and PHBS. Conclusion: It can be concluded that the better the level of students’ health knowledge, the better the implementation of clean and healthy living behavior.